Enacting reflective and deliberative practices in action research. (3rd September 2019) - Forester, John; Kuitenbrouwer, Martien; Laws, David
ABSTRACT: We consider action research as a form of deliberative policy analysis. This analysis explores a "reconstruction clinic" in which stakeholders and public officials engaged memories, hopes and obligations as they sought to resolve controversies over details of policy implementation. We ask how institutional design shaped participants' reflective and deliberative progress. Reflection in action can prompt not only changes in cognitive frames, but new behavioural capacities for action. Deliberative practices can shape new relationships between parties through the work of apology, recognition, appreciation, and emergent collaboration.